Wetting-drying behaviour of geogrid-reinforced clay under working load conditions. Issue 3 (1st June 2010) - Pathak, Y.P.; Alfaro, M.C.
Abstract : ABSTRACT: Large-scale plane-strain laboratory wetting–drying tests on geosynthetic-reinforced and unreinforced expansive clay specimens were performed to assess the interaction between geogrid and clay during wetting and drying. Independent vertical and lateral pressures were applied to the specimens to simulate anisotropic loading condition in the field. The wetting and drying processes were simulated by flooding the test specimens with water and subsequently removing water from the test box for drying the test specimens. Further drying of the test specimens was done by circulating warm air of about 35°C on both top and bottom of the test specimens. Geogrid reinforcement strains, soil specimen deformations, soil suctions and soil temperatures were monitored during the wetting–drying process. Additional strains were observed in the geogrid reinforcement due to a wetting–drying cycle of the expansive clay specimens. These strain levels were however considered minimal (less than 1% strain) to cause overstressing in the reinforcement. Overall, the geogrid reinforcement reduced the swelling of clay specimens.